2014
DOI: 10.1186/1471-2377-14-112
|View full text |Cite
|
Sign up to set email alerts
|

Dementia with Lewy bodies versus nonconvulsive status epilepticus in the diagnosis of a patient with cognitive dysfunction, complex visual hallucinations and periodic abnormal waves in EEG: a case report

Abstract: BackgroundThe diagnosis of dementia with Lewy bodies (DLB) is often challenging in elderly individuals, not only for its various clinical features, sometimes, but also for its rare changes of periodic synchronous discharges (PSD) in electroencephalogram ( EEG). So, we reported one case of DLB and gave a detailed analysis.Case presentationA Chinese patient (Female, 56 years old) presented with progressive cognitive decline and complex visual hallucinations. Several days after admission, she gradually showed foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Our hypothesis that DLB could predispose a person to seizures, similar to that seen in other neurodegenerative disorders such as AD or VaD, is supported by a similar case report from Sun et al where a patient with DLB presented with focal myoclonic jerks and EEG abnormalities 16. In 2008, Roks et al also reported that EEG abnormalities—mainly in the frontal areas—could be supportive of the diagnosis of DLB but did not describe clinically evident seizure activity 17…”
Section: Discussionsupporting
confidence: 69%
“…Our hypothesis that DLB could predispose a person to seizures, similar to that seen in other neurodegenerative disorders such as AD or VaD, is supported by a similar case report from Sun et al where a patient with DLB presented with focal myoclonic jerks and EEG abnormalities 16. In 2008, Roks et al also reported that EEG abnormalities—mainly in the frontal areas—could be supportive of the diagnosis of DLB but did not describe clinically evident seizure activity 17…”
Section: Discussionsupporting
confidence: 69%
“…The abnormalities in the EEG observed in this patient are likely related to a non‐convulsive status epilepticus and, in the late stage of disease, to sporadic CJD. However, periodic EEG might occasionally occur in other neurodegenerative illnesses, including LBD, AD or vascular encephalopathy …”
Section: Discussionmentioning
confidence: 99%
“…Patients with Lewy body dementia (DLB) have a higher risk of developing seizures than the general population 1 . Case reports have shown that patients with DLB may present with epilepsy 2,3 or patients with epilepsy showing symptoms mimicking DLB 4 . Further, since the early features of DLB may bear resemblance to nonconvulsive seizures, as for example, fluctuating cognition, a common feature in patient with DLB, 5 seizures may go undetected as has been shown in patients with Alzheimer's disease (AD) 1 …”
Section: Introductionmentioning
confidence: 99%